The Stability of the Gold Standard and the Evolution of the International Monetary System - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 1995)
This paper examines some popular explanations for the smooth operation of the pre-1914 gold standard. We find that the rapid adjustment of economies to underlying disturbances played an important role in stabilizing output and employment under the gold standard system, but no evidence that this success also reflected relatively small underlying disturbances. Finally, the paper also suggests an explanation for the evolution of the international monetary system based on growing nominal inertia over time.